Pemberdayaan Anggota Kelompok Wanita Tani Melalui Optimalisasi Pekarangan Pangan Lestari di Kecamatan Palimanan Kabupaten Cirebon: Empowering women farmer group members through optimizing suistanable food yards in Palimanan sub-district Cirebon Regency - Asri Suhartianah; Tri Ratna Sari Dewi; Nazaruddin (Jurnal Penyuluhan Pertanian, 2022)
The proper use of yard land greatly contributes to food security and health. The problem faced is that the knowledge of housewives about agricultural cultivation techniques is still low, so it is necessary to empower for the use of yard land. This research aims to (1) describe empowerment (2) analyze the factors that influence empowerment (3) develop a strategy for empowering women farmer group members through optimizing sustainable food yards. The research was conducted in Palimanan District, Cirebon Regency, starting from April to July 2021. The entire population of this research was 53 people spread over 3 selected villages. Data were analyzed descriptively and multiple linear regression analysis. The results showed that the empowerment of women farmer groups in Palimanan District was in the moderate category. Factors that influence the empowerment of women's farmer groups are age, function of women's farmer groups, support for extension services, and environmental support. The strategies for empowering women farmer groups through optimizing sustainable food yards are: 1) Conducting discussions together by approaching adults and sharing experiences 2) Carrying out intensive use of yard land by improving the quality of counseling 3) Improving the functions of women farmer groups including: class learning, cooperation vehicles, and production units. 4) Increasing the empowerment of women's farmer groups towards agricultural business through the use of yard land through.